ADMINISTRASI PEMBANGUNAN MENGHADAPI REVOLUSI 4.0 - Asep Hidayat (Media Bina Ilmiah, 2023)
a review of development administration in revolution 4.0. This industrial revolution was first introduced in Europe by starting with the invention of the steam and water power engine known as the Industrial Revolution 1.0 and continues to grow until now which has reached the era of the Industrial Revolution 4.0. In the Industrial Revolution 4.0, it will focus on how to utilize existing technology, collaborate and develop it in all aspects, including in the administration of this development. So that the government is required to be ready and alert to implement this. In addition, they must also be able to find ways to collaborate, provide innovation, and utilize information and communication technology.